2010
DOI: 10.1128/jvi.01310-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Tumor Necrosis Factor Alpha (TNF-α) Receptor and Interleukin-1 Receptor Knockout Mice Reveals a Link between TNF-α Signaling and Increased Severity of 1918 Pandemic Influenza Virus Infection

Abstract: The influenza pandemic of 1918 to 1919 was one of the worst global pandemics in recent history. The highly pathogenic nature of the 1918 virus is thought to be mediated in part by a dysregulation of the host response, including an exacerbated proinflammatory cytokine response. In the present study, we compared the host transcriptional response to infection with the reconstructed 1918 virus in wild-type, tumor necrosis factor (TNF) receptor-1 knockout (TNFRKO), and interleukin-1 (IL-1) receptor-1 knockout (IL1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…It is possible that at least some of the effects of IL-1R1 deficiency that we have observed, however, may reflect not only loss of IL-1 signaling, but also compensation by other cytokines due to genetic deletion of IL-1R1 over the entire life span of these mice. Indeed, previous studies have observed increased TNF-α production after Klebsiella pneumoniae or influenza virus infection in mice with life-long genetic inactivation of IL-1 signaling (68,69). If such compensatory increases in proinflammatory cytokines have occurred in our IL-1R1-deficient mice, results may not reflect the effects of inhibition of IL-1 in adult mice with a pharmacological agent.…”
mentioning
confidence: 83%
“…It is possible that at least some of the effects of IL-1R1 deficiency that we have observed, however, may reflect not only loss of IL-1 signaling, but also compensation by other cytokines due to genetic deletion of IL-1R1 over the entire life span of these mice. Indeed, previous studies have observed increased TNF-α production after Klebsiella pneumoniae or influenza virus infection in mice with life-long genetic inactivation of IL-1 signaling (68,69). If such compensatory increases in proinflammatory cytokines have occurred in our IL-1R1-deficient mice, results may not reflect the effects of inhibition of IL-1 in adult mice with a pharmacological agent.…”
mentioning
confidence: 83%
“…In agreement with our study, these studies report the lack of involvement of TNFR1 in influenza viral clearance. 26,27 However, infected TNFR1-deficient mice had a significant delay in weight loss compared to WT from day 3 to 8 after infection, although they ultimately succumbed. 26,27 On one hand, these findings lend further support to the current belief that TNF-␣ is a proimmune or proinflammatory cytokine, particularly in the early response (first 7 days of infection) and that a "cytokine storm" may contribute to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, infected TNFR1-deficient mice had a significant delay in weight loss compared to WT from day 3 to 8 after infection, although they ultimately succumbed. 26,27 On one hand, these findings lend further support to the current belief that TNF-␣ is a proimmune or proinflammatory cytokine, particularly in the early response (first 7 days of infection) and that a "cytokine storm" may contribute to disease severity. [23][24][25] On the other hand, these findings differ from our current results with respect to the role of TNF-␣ in influenza disease severity and immunopathology, which is likely due to the choice of model influenza viruses of different pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis of statistically significant gene expression changes was performed using the Ingenuity Pathways Knowledge Base (IPA; Ingenuity Systems) as previously described (4). All enrichment scores were calculated in IPA using all probes that passed our QC filter as the background data set.…”
mentioning
confidence: 99%